2010
DOI: 10.1186/1472-6963-10-41
|View full text |Cite
|
Sign up to set email alerts
|

Empirical aspects of record linkage across multiple data sets using statistical linkage keys: the experience of the PIAC cohort study

Abstract: BackgroundIn Australia, many community service program data collections developed over the last decade, including several for aged care programs, contain a statistical linkage key (SLK) to enable derivation of client-level data. In addition, a common SLK is now used in many collections to facilitate the statistical examination of cross-program use. In 2005, the Pathways in Aged Care (PIAC) cohort study was funded to create a linked aged care database using the common SLK to enable analysis of pathways through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 8 publications
(7 reference statements)
2
44
0
1
Order By: Relevance
“…Além disso, as variáveis de confirmação do linkage, como "nome da mãe" e "endereço de residência", também apresentavam baixa completitude, respectivamente, 0,5 e 23,6%. No estudo de Karmel et al 25 , que objetivou descrever os aspectos empíricos da técnica de linkage, foi observado que a presença de valores ignorados diminuiu a probabilidade de identificar um par verdadeiro.…”
Section: Resultsunclassified
“…Além disso, as variáveis de confirmação do linkage, como "nome da mãe" e "endereço de residência", também apresentavam baixa completitude, respectivamente, 0,5 e 23,6%. No estudo de Karmel et al 25 , que objetivou descrever os aspectos empíricos da técnica de linkage, foi observado que a presença de valores ignorados diminuiu a probabilidade de identificar um par verdadeiro.…”
Section: Resultsunclassified
“…However, the use of an SLK in addition to person-level data items such as area of usual residence and date of health care episode has been shown, using a stepwise deterministic matching algorithm, to achieve 0.5% false positive links between aged care and residential/community care databases. 19 This approach also achieved a PPV of 97% and a sensitivity of 95% for linkage between hospitalisation and residential aged care records. 20 A previous study found that the use of alias names may affect the quality of name data held on the various registers for these individuals.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the relative accuracy of simple deterministic record linkage using a statistical linkage key, such as the SLK‐581, which incorporates five letters of the name (three letters of the family name and two letters of the given name), the eight digit date of birth, and sex of the registrant, is uncertain. However, the use of an SLK in addition to person‐level data items such as area of usual residence and date of health care episode has been shown, using a stepwise deterministic matching algorithm, to achieve 0.5% false positive links between aged care and residential/community care databases 19 . This approach also achieved a PPV of 97% and a sensitivity of 95% for linkage between hospitalisation and residential aged care records 20…”
Section: Discussionmentioning
confidence: 99%
“…Previous work [18] suggested at least two widely used and suitable encryption methods for privacy preserving record linkage in the given context: The Swiss Anonymous Linking Code (Swiss ALC [16]) and the Encrypted Statistical Linkage Key (Australian ALC [17]). The Swiss ALC concatenates the Soundex codes of first and last name, sex and date of birth.…”
Section: ) Anonymous Linking Codesmentioning
confidence: 99%
“…After the phonetic encoding, the resulting codes are usually combined with additional identifiers, such as date of birth and sex, which are finally encrypted with keyed HMACs. Examples for these kind of linkage keys are given by [16] and [17]. Statistical linkage keys usually produce acceptable results and seem to be safe against most cryptographic attacks.…”
Section: Introductionmentioning
confidence: 99%